Analysis of Building Information Modeling (BIM) Implementation in Mechanical, Electrical, and Plumbing (MEP) Works on the Success of Construction Projects - Putri, Mike Riska (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
The construction industry has an important role in global infrastructure development, with Building Information Modeling (BIM) an increasingly important innovation to improve efficiency, collaboration and project quality. The transformation of the construction industry that is developing from Industrial Revolution 4.0 to Society 5.0 requires the use of technology that takes advantage of the connection between humans and digital systems. Even though BIM offers great potential in the construction sector, its implementation in Mechanical, Electrical and Plumbing (MEP) work still faces major challenges such as communication barriers, communications and the risk of delays which affect the final project results. The aim of this research is to identify the factors that influence the successful implementation of BIM in MEP work, as well as the benefits and barriers that arise in the field. The analysis method used is factor, namely a multivariate statistical technique that groups mutually inhibiting variables into main factors that can influence the effectiveness of BIM implementation. The research results show that the application of BIM to MEP work provides benefits to the quality of MEP project management, MEP project performance and operational efficiency of MEP work. BIM implementation also has obstacles caused by policy factors, organizational factors and knowledge factors in implementing BIM in MEP work. The Human Resources (HR) readiness factor is the main aspect that influences the success of implementing BIM in MEP work.